UZBEK NOVELS OF THE PERIOD OF INDEPENDENCE ARE BASED ON SYMBOLIC POETICS. (ON THE EXAMPLE OF THE NOVEL BY AHMAD AZAM "REALITY OR JOURNEY TO THE SLAVE SPACE") - Hamdamov Ulugbek Abduvakhobovich (Scholar Express Journals, 2021)
The article examines the problem of symbolic poetics on the example of the novel by Ahmad Azam "Reality or Journey to the Slave Space". For comparison, the "Feast of Demons" by Abdullah Qadiri and "The Lost One" by Rahimjon Rahmat will be analyzed.
Keywords: Genre of the novel; symbol; plot of the novel; pattern